Distributed deep reinforcement learning for autonomous aerial eVTOL mobility in drone taxi applications - Yun, Won Joon; Jung, Soyi; Kim, Joongheon; Kim, Jae Hyun (ICT Express, 2021)
The urban aerial mobility (UAM) system, such as drone taxi or air taxi, is one of future on-demand transportation networks. Among them, electric vertical takeoff and landing (eVTOL) is one of UAM systems that is for identifying the locations of passengers, flying to the positions where the passengers are located, loading the passengers, and delivering the passengers to their destinations. In this paper, we propose a distributed deep reinforcement learning where the agents are formulated as eVTOL vehicles that can compute the optimal passenger transportation routes under the consideration of passenger behaviors, collisions among eVTOL, and eVTOL battery status.
Keywords: Air taxi; Distributed deep reinforcement learning; Drone taxi; eVTOL; Urban aerial mobility